Sovereign Borrowing Cost and the IMF's Data Standards Initiatives - Cady, John (IMF Working Papers; Working Paper ;, 2006)
The effects of the IMF's data standards initiatives on sovereign borrowing costs in private capital markets are investigated for 26 emerging market and developing countries. Stable and significant panel econometric estimates indicate that subscription to the Special Data Dissemination Standard (SDDS) reduces launch spreads by an average of 20 percent while participation in the General Data Dissemination System (GDDS) reduces spreads for those countries with access to capital markets by an average of 8 percent. These estimates correspond to discounts of some 50 and 20 basis points, respectively. Evidence of similar discounts is also found when launch yields are analyzed.